Measurement by the physical educator : - Miller, David K (McGraw-Hill, 2006)
Providing a solid foundation in measurement and evaluation, this text helps your students learn how to measure physical performance, construct and select tests, and grade the results. Students also get hands-on experience in practicing with statistical techniques, using the computer, choosing the appropriate test, and designing a new test.